Attendance management system using selfies and signatures. (2018) - Iio, Jun
There have been multiple proposals to optimise student attendance management in higher education. However, each method has pros and cons and we have not yet found a perfect solution. In this study, a novel framework for attendance management is proposed that consists of a mobile device and a web application. During lectures, students participating in the lecture can register their attendance on the mobile device with their selfie or their signature. After the lecture is finished, the registration data are sent to the database and they are added to the 'RollSheet'. This paper reports an overview of this system and the results of an evaluation after a trial period, which was conducted in the second semester of the 2015 fiscal year.